Primary Mental Health Care for Institutionalized Children and Adolescents: A Health Team Perspective [Salud Mental Primaria Para Niños, Niñas y Adolescentes Institucionalizados: Perspectiva de Equipos de Salud] - Martinez-Diaz, P (Revista Latinoamericana de Ciencias Sociales, 2021)
Mental health care for vulnerable and institutionalized children and adolescents is a clinical and ethical challenge in Chile and Latin America. This study explores experiences and challenges encountered when providing mental health care among primary health care professionals. Qualitative research was conducted using an openended questionnaire for interviewing professionals in a rural area of Chile. The data was analyzed using Grounded Theory. The results show a fragmented and discontinuous delivery of care as a large portion of the children s clinical and social history is unknown. There is lack of coordination with other institutions that intervene in this area. The authors discuss implications for primary health care training for children s mental health teams and the need for the implementation of effective integrated and multilevel care systems. © The Author(s), 2021.